Analisis Kesenjangan Keterampilan (Skill Gap) Mahasiswa dengan Kebutuhan Industri di Era Revolusi Industri 4.0 - Sri Maharani; Erwin Permana (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2026)
This study aims to analyze the skills gap in the era of the Industrial Revolution 4.0 and the factors influencing it. The research employed a descriptive-analytical approach based on literature studies and the author’s analysis of the dynamics of formal education curricula and the development of industrial needs. The findings indicate that formal education curricula that are less adaptive to technological developments are the main factor causing the skills gap. In addition, the slow adaptation to technology in educational and industrial environments, as well as the unequal distribution of skills development across various regions in Indonesia, further widen the gap between graduates’ competencies and labor market demands. This condition affects the low readiness of the workforce in facing digital transformation and global competition. The study concludes that the skills gap is a strategic issue requiring serious attention from the government, educational institutions, and the industrial sector. Curriculum reform that is responsive to technological advancements, strengthening digital literacy, and ensuring equal access to training and skills development are essential steps to improve the competitiveness of Indonesian human resources. These efforts are expected to support poverty reduction, reduce social inequality, and achieve the long-term national development goals toward Indonesia Golden Vision 2045.